Navigation Techniques in Endoscopic Spine Surgery. (29th August 2022) - Hagan, Matthew J.; Remacle, Thibault; Leary, Owen P.; Feler, Joshua; Shaaya, Elias; Ali, Rohaid; Zheng, Bryan; Bajaj, Ankush; Traupe, Erik; Kraus, Michael; Zhou, Yue; Fridley, Jared S.; et al.
Abstract : Endoscopic spine surgery (ESS) advances the principles of minimally invasive surgery, including minor collateral tissue damage, reduced blood loss, and faster recovery times. ESS allows for direct access to the spine through small incisions and direct visualization of spinal pathology via an endoscope. While this technique has many applications, there is a steep learning curve when adopting ESS into a surgeon's practice. Two types of navigation, optical and electromagnetic, may allow for widespread utilization of ESS by engendering improved orientation to surgical anatomy and reduced complication rates. The present review discusses these two available navigation technologies and their application in endoscopic procedures by providing case examples. Furthermore, we report on the future directions of navigation within the discipline of ESS.